Pengaruh Kondisi Ekonomi Keluarga Terhadap Hasil Belajar Melalui Motivasi Belajar Siswa SMKN 8 Bandar Lampung - Verani, Desti; Rahmwati, Rahmawati; Pujiati, Pujiati; Rusman, Tedi (Journal of Social Science Education, 2025)
Education is a conscious and planned effort to create a learning atmosphere and a learning process for students which is carried out actively to develop their potential in the form of religious spiritual strength, self-control, personality, intelligence and noble morals. Education is an important priority that is used as an investment for the future. The benchmark for educational success can be seen from learning outcomes which can be influenced by various factors, including family economic conditions and student learning motivation. This research aims to determine the influence of economic conditions on the learning outcomes of students majoring in financial accounting at SMK Negeri 8 Bandar Lampung through learning motivation as a moderating variable. The research method used is descriptive verification with a survey and ex post facto approach. The population in this study were all students majoring in financial accounting at SMK Negeri 8 Bandar Lampung for the 2023/2024 academic year. The sample used in this research was 172 students with a sampling technique using probability sampling, simple random sampling method. Hypothesis testing analysis was partially carried out through the t test and simultaneously carried out through the F test. The results of this research show that the value in the Coefficients table obtained t-count > t-table or 4.049 > 1.974 and a significant value of 0.000 < 0.05, thus stating the economic condition of the family influence on student learning motivation. The family economic condition variable has no effect on student learning outcomes, this is proven by the t-count > t-table or 0.557 < 1.974 and a significant value of 0.579 > 0.05. The results of research on the variables of learning motivation and learning outcomes show that the t-value < t-table or 2.288 > 1.974 and the significant value is 0.000 < 0.05, thus stating that learning motivation has an influence on student learning outcomes. The higher the level of learning motivation that students have, the better the learning outcomes that students obtain in the learning process.Keywords: Learning Outcomes, Family Economic Conditions, Learning Motivation